Kadra Narodowa-Lechia Gdańsk. (Gdańsk : [s.n.], 1955)
Afisz inform. o meczu na stadionie we Gdańsku-Wrzeszczu 13.07.1955 r.
Keywords: Lechia Gdańsk -- 1945-1970 -- druki ulotne; Piłka nożna -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne